On improved Z-R Relation Derived from Czech Distrometer Data - Kovalchuk, Maria; Zikešová, Aneta; Albakawe, Ahmad; Fišer, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The contribution deals with the analysis of DSD (Drop Size Distribution) data measured by the videodistrometer, which is operated by the Institute of the Atmospheric Physics of Czech Academy in Prague.The radar reflectivity factor and rain intensity are precisely calculated from the measured DSDs through pertinent formulas. Using the regression method, we then looked for a power law relation between these quantities, which would better suit the Czech climate conditions than the more general published relationships. After finding a relationship for all DSDs analysed one-minute DSDs, we then classified the rains according to the rain intensity (above and below 5 mm/h). We further categorized rains as the stratiform and convective types. For this, we used 3 criteria that are based on DSD parameters of analytical approximations. We have come to the conclusion that if we know more about the rain (whether it is convective or stratiform), we can determine the approximate relationship between the radar reflectivity factor and the intensity of rain more accurately. After 3 criteria we used, rain categorization appears to be the most accurate according to J. Testud's criterion.
O vylepšené Z-R relace, odvozené z dat z českého distrometru
Keywords: Reflectivity; Meteorological radar; Rain; Atmospheric measurements; Radar measurements; Estimation; Size measurement; Odrazivost; Meteorologický radar; Déšť; Měření atmosféry; Radarové měření; Estimace; Velikostní měření